Antioxidant potential, cytotoxic activity and total phenolic content of Alpinia pahangensis rhizomes - Phang, C.W.; Abd Malek, S.N.; Ibrahim, H. (BioMed Central, 2013)
Background: Alpinia pahangensis, a wild ginger distributed in the lowlands of Pahang, Malaysia, is used by the locals to treat flatulence. In this study, the antioxidant and cytotoxic activities of the crude aqueous methanol and fractionated extracts of Alpinia pahangensis against five different cancer and one normal cell lines were investigated. The total phenolic content of each extract and its fractions were also quantified. This is the first report on the antioxidant and cytotoxic activities of Alpinia pahangensis extract. Methods: In the current study, the crude methanol and fractionated extract of the rhizomes of Alpinia pahangensis were investigated for their antioxidant activity using four different assays namely, the DPPH scavenging activity, superoxide anion scavenging, β-carotene bleaching and reducing power assays whilst their phenolic contents were measured by the Folin-Ciocalteu’s method. In vitro neutral red cytotoxicity assay was employed to evaluate the cytotoxic activity against five different cancer cell lines, colon cancer (HCT 116 and HT-29), cervical cancer (Ca Ski), breast cancer (MCF7) and lung cancer (A549) cell lines, and one normal cell line (MRC-5). The extract that showed high cytotoxic activity was further investigated for its chemical constituents by GC-MS (gas chromatography–mass spectrometry) analysis. Results: The ethyl acetate fraction showed the strongest DPPH radical scavenging (0.35 ± 0.094 mg/ml) and SOD activities (51.77 ± 4.9%) whilst the methanol extract showed the highest reducing power and also the strongest antioxidant activity in the β-carotene bleaching assays in comparison to other fractions. The highest phenolic content was found in the ethyl acetate fraction, followed by the crude methanol extract, hexane and water fractions. The results showed a positive correlation between total phenolic content with DPPH radical scavenging capacities and SOD activities. The hexane fraction showed potent cytotoxic effect against KB, Ca Ski and HCT 116 cell lines with IC50 of 5.8 ± 0.1 and 9.1 ± 2.0 ug/ml, respectively. The major components of hexane fraction analysed by GC-MS analysis were mostly methyl esters. Conclusions: The current study suggests that the methanol extract and ethyl acetate fraction of A. pahangensis is a potential source of natural antioxidant for protective as well as prevention of life-threatening diseases. The hexane fraction of A. pahangensis may have the potential to be developed into therapeutic option for treating cancer.